UNODA Occasional Papers No.18: Ways to Strengthen the Field of Verification, January 2010 - United Nations Office for Disarmament Affairs (United Nations, 2012)
The United Nations Office for Disarmament Affairs (UNODA) Occasional Papers is a series of ad hoc publications presenting, in edited form, papers or statements made at meetings, symposiums, seminars, workshops or lectures that deal with topical issues in the field of arms limitation, disarmament and international security. They are intended primarily for those concerned with these matters in Government, civil society and in the academic community. They deal with topical issues in the field of arms limitation, disarmament and international security and are intended primarily for those concerned with these matters in Government, civil society and in the academic community. The subject of this issue is “ways to strengthen the field of verification”, and is presented by two papers in this publication.